Le kenningar come elementi formulari nelle Friðþjófsrímur islandesi, in La retorica tra oralità e scrittura nella tradizione germanica - Lombardi Maria Cristina (UniorPress, 2024)
Kennings have sometimes been regarded as formulas or formula-like devices belonging to an old oral tradition going back to poets who composed their poems orally. Their position as closely dependent on metric requirements is particularly evident in late Medieval poetry, especially in Icelandic rímur, a peculiar Icelandic poetic genre, where the presence of kennings is overwhelming and their role is clearly connected with metrics. This paper aims to show how kennings (in Friðþjófsrímur) vary with metric changes, playing a formula-like role in a genre which is a remake of prose narratives (sagas), and, as far as kennings are concerned, draws on pre-fabricated lists, mostly Snorri’s or even rune-poems periphrases.